2020
DOI: 10.1007/s41999-020-00294-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and functionality in geriatric rehabilitation patients: a systematic review and meta-analysis

Abstract: Aim This systematic review and meta-analysis aims to characterize the nutritional status of geriatric rehabilitation patients and its association with functional parameters. Findings Malnutrition is prevalent in a relevant percentage of geriatric rehabilitation patients, whereas body mass index (BMI) is in the normal to overweight range. Furthermore, data suggest that protein and energy intake is reduced and vitamin D deficiency is prevalent in this population. Decreased physical function is associated with ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 92 publications
2
49
2
3
Order By: Relevance
“…Geriatric rehabilitation following an acute event aims at functional recovery through multidisciplinary interventions [1]. Onethird of geriatric rehabilitation patients are diagnosed with malnutrition [2], which is a modifiable risk factor of sarcopenia [3], the age-related low muscle strength and muscle mass [4], being present in 56% of geriatric rehabilitation patients [5]. Malnutrition and sarcopenia are independently associated with functional decline [6,7], lower quality of life [8,9] and higher mortality [10,11] in older adults and can negatively impact functional recovery during geriatric rehabilitation [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Geriatric rehabilitation following an acute event aims at functional recovery through multidisciplinary interventions [1]. Onethird of geriatric rehabilitation patients are diagnosed with malnutrition [2], which is a modifiable risk factor of sarcopenia [3], the age-related low muscle strength and muscle mass [4], being present in 56% of geriatric rehabilitation patients [5]. Malnutrition and sarcopenia are independently associated with functional decline [6,7], lower quality of life [8,9] and higher mortality [10,11] in older adults and can negatively impact functional recovery during geriatric rehabilitation [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that nutritional status is associated with functional outcomes in geriatric rehabilitation patients [ 1 , 2 ] and malnutrition was associated with a decreased improvement in activities of daily living (ADL) over the course of geriatric rehabilitation [ 2 ]. However, the relevance of obesity for functional outcomes has only rarely been investigated in this setting, although this seems particularly relevant in view of the obesity pandemic in old age.…”
Section: Introductionmentioning
confidence: 99%
“…The latter point is particularly problematic given that the primary outcome for most prehabilitation trials was identified to be functional and/or clinical. Malnourished patients have lower functional capacity (58,64) and a reduced capacity to gain function through exercise alone (without first correcting malnutrition, which, for malnourished patients, could be the underlying etiology for the compromised function (58,65,66). A failure to correctly identify malnutrition for treatment has the potential to produce misleading findings for the effect of prehabilitation.…”
Section: Discussionmentioning
confidence: 99%